2012
DOI: 10.1111/j.1740-0929.2012.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of screening method for intestinal mucus adhesive lactobacilli using the enzymatic activity of glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH)

Abstract: Adhesion tests are complex, time-consuming and expensive, while the most important criterion for a probiotic lactobacilli is the ability to adhere to the human intestine. Thirty lactobacilli isolates from human intestinal tissues were measured for cell surface glyceraldehyde-3-phosphate dehydrogenase (GAPDH) activity using a microtiter plate screening method. GAPDH activities were detected in 21 out of 30 samples from 12 h cultures and in all samples from 18 h cultures. This suggests GAPDH is universally expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…A 4Á18-fold increased abundance of glyceraldehyde 3-phosphate dehydrogenase (Gap) was observed in strain DRR12 in response to acid (Table 3). Association of Gap to the cell envelope has been previously reported in other bacteria (Pancholi and Fischetti 1992;Ruiz et al 2009) including lactobacilli (Antikainen et al 2007;Nezhad et al 2012;Kinoshita et al 2013). Interestingly, Antikainen et al (2007) observed that Gap is associated to the cell envelope in Lactobacillus crispatus at acidic pH, whereas at neutral pH is rapidly released to the media and that Gap interacts with negatively charged LTAs.…”
Section: Discussionmentioning
confidence: 65%
“…A 4Á18-fold increased abundance of glyceraldehyde 3-phosphate dehydrogenase (Gap) was observed in strain DRR12 in response to acid (Table 3). Association of Gap to the cell envelope has been previously reported in other bacteria (Pancholi and Fischetti 1992;Ruiz et al 2009) including lactobacilli (Antikainen et al 2007;Nezhad et al 2012;Kinoshita et al 2013). Interestingly, Antikainen et al (2007) observed that Gap is associated to the cell envelope in Lactobacillus crispatus at acidic pH, whereas at neutral pH is rapidly released to the media and that Gap interacts with negatively charged LTAs.…”
Section: Discussionmentioning
confidence: 65%
“…The role of the GAPDH protein as an adhesin was confirmed in various bacterial species, including numerous bacteria from the genus Lactobacillus (Kainulainen et al, 2012;Kinoshita et al, 2012;Terrasse et al, 2015). The role of the TUFM protein in promoting the adhesion of bacteria (e.g.…”
Section: Detection Of Gapdh and Tufm In Extracellular Protein Fractiomentioning
confidence: 93%
“…To explore the impact of enzyme activity, GAPDH solution (2 mg/mL) was heated at 50 or 60°C for 1–3 h. GAPDH activity was evaluated according to the method described by Kinoshita et al . Briefly, 1 μL of glyceraldehyde‐3‐phosphate (47 mg/mL, Sigma‐Aldrich), 25 μL of NAD + (10 mM, Roche Diagnostics GmbH) and 175 μL of assay buffer (40 mM triethanolamine, 50 mM Na 2 HPO 4 , 0.2 mM ethylenediaminetetraacetic acid, 20 mM 2‐mercaptoethanol and 0.1% (v/v) Tween 20, pH 8.5) were added in 50 μL of each sample.…”
Section: Methodsmentioning
confidence: 99%